The Impact of Perceived Country of origin Image on Purchasing Intention of Mobile Users in Sudan - Abdel Karim, Maysoun Ali; Hamed, Abdul Salam Adam; Abdullah, Mohammed Issa (Journal of Economic, Administrative and Legal Sciences, 2019)
The country of origin considered as one of most effect factors on consumers' evaluation of the product as an external feature is one of the most important topics related to international marketing and the country of origin is usually linked to the word "made in ..." which is an intangible feature of the product similar to the guarantee and brand name, it does not directly affect the real performance of the product, as well as the country of origin is an important element of marketing is known to affect the perceptions of consumers as well as their behavior leading to the consumer cognitive situation, This study used the descriptive method and aimed to measure the level of customer perception of the image of country of origin, and the impact of image of country of origin (Economics, Technological, Human Resource, and Political dimensions) on purchase intention, the population of the study graduate students (Master) in Sudan universities, (Khartoum state) and the data were collected through questionnaire from non- probability , convenience sample consisting of (300) respondent, and hypotheses have been tested by regression, and another statistical tools (standard deviations, means) by using (SMART PLS) The study found that There is no positive relationship between the economic and technological dimensions and the purchasing intention. Also found there is positive relationship between economic and technological dimensions and purchasing intention. The study also found that there are significant differences in respondents' answers due to Personal characteristics (gender) of economy and human resources only, the study recommend decision makers of cell phone companies to provides a clear information about economical and human capital of country of origin, The consumer's perception of the country of origin through these two dimensions has a significant impact on purchasing intention, As well as taking into account the differences between males and females with regard to the information on which each based on the realization of product value and provide customized promotional efforts. The study also recommended that future studies focus on further research on the relationship between country image and purchasing behavior.
Keywords: country of origin; the perceived image of the country of origin; purchasing intention